RELATIONSHIP BETWEEN DURATION OF UNTREATED PSYCHOSIS AND COGNITIVE FUNCTIONS USING MODIFIED SCORS (SCHIZOPHRENIA COGNITION RATING SCALE) IN SCHIZOPHRENIA PATIENTS IN SAIFUL ANWAR GENERAL HOSPITAL - Dearisa Surya Yudhantara; Laksmi Muliawati; Zamroni Afif (Journal of Psychiatry Psychology and Behavioral Research, 2021)
Mental health is a significant health problem in the world, including Indonesia. Lack of understanding and concern for the community, limitations and unequal distribution of mental health service provider also contribute to obstacles to increase public understanding and concern for mental health. This problem will give an impact on the difficulty of patients in accessing care and treatment. The emergence of the phenomenon of Duration of Untreated Psychosis (DUP) or untreated psychosis in society contributes to the worsening of the disease course of schizophrenic patients. One of the main clinical manifestations seen in schizophrenic patients is a decline in cognitive function. SCoRS is present as an easy and effective instrument in quantitatively measuring cognitive function. In the study used a modified SCoRS instrument that was more adapted to Indonesian’s culture. This study was conducted to determine the relationship between the duration of untreated psychosis and cognitive function using modified SCoRS, especially in schizophrenic patients at Saiful Anwar General Hospital. The research method used observational analytic with a cross-sectional approach. Selection of research subjects based on inclusion and exclusion criteria. Then do the appropriate history taking and psychiatric examination. Correlation analysis using Spearman to determine the relationship of variable duration of psychosis without therapy and cognitive function assessed using SCoRS modification (p <0.05). The results prove that there is a significant relationship between the variable duration of therapy without therapy and cognitive function variables assessed using SCoRS modification with a weak correlation level (correlation coefficient 0.340).